Emergent Invasive Group A Streptococcus dysgalactiae subsp. equisimilis, United States, 2015–2018 - Sopio Chochua; Joy Rivers; Saundra Mathis; Zhongya Li; Srinivasan Velusamy; Lesley McGee; Chris Van Beneden; Yuan Li; Benjamin J. Metcalf; Bernard Beall (Emerging Infectious Diseases, 2019)
The term group A Streptococcus is considered synonymous for the species Streptococcus pyogenes. We describe an emergent invasive S. dysgalactiae subspecies equisimilis lineage that obtained the group A antigen through a single ancestral recombination event between a group C S. dysgalactiae subsp. equisimilis strain and a group A S. pyogenes strain.